PROFITABILITAS SEBAGAI INTERVENING TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Jasa Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Mohklas, Mohklas; Pancawardani, Nurul Latifah (JAB (Jurnal Akuntansi & Bisnis), 2020)
Purpose of this study was to analyze the effect of Independent Commissioner Board Proportion, Institutional Ownership, Company Size on Tax Avoidance through Profitability. The research object of property and real estate sector companies listed on the Indonesia Stock Exchange for the period 2016-2018, the sampling system uses a purposive sampling method. The number of samples of 45 companies that meet the criteria.Research variable; The proportion of the Independent Board of Commissioners, Institutional Ownership, and Company Size as independent variables, Profitability being the mediating variable, while Tax Avoidance as the dependent variable. Data analysis using hypothesis test (t-test), path analysis.The results of the research by the board of commissioners, institutional ownership and firm size have an effect on profitability. The board of commissioners, company size and profitability have an effect on tax avoidance, while institutional ownership has no effect.Direct effect of the board of commissioners on tax avoidance is 0.188 while the indirect effect is -1,90 through profitability, so the total effect is -1,71. Institutional ownership has a direct effect of 1.797 while the indirect effect is -2.255 so that the total influence is -0.258. Company size has a direct effect of -0.407 while the indirect effect is 0.341, so the total effect is - 0.065.Â Keywords: Independent Commissioner Board Proportion, Institutional Ownership, Company Size, Profitability and Tax Avoidance.